Governing factors of the record-breaking marine heatwave over the mid-latitude western North Pacific in the summer of 2021 - Pak, Gyundo; Noh, Joocheul; Park, Young-Gyu; Jin, Hyunkeun; Park, Jae-Hyoung (Frontiers in Marine Science, 2022)
During July of 2021, the sea surface temperature of the mid-latitude western North Pacific had increased by five degrees over 10 days. This high temperature was maintained for approximately a month before it disappeared rapidly in approximately five days. The underlying mechanisms of this unprecedented marine heatwave event have not yet been researched through a quantitative approach. The development and decay processes of the marine heatwave event were investigated using heat budget analysis and one-dimensional modeling. In mid-July, an anomalous high-pressure atmospheric circulation, affecting to the reduced cloud coverage and increased solar radiation, anchored where the marine heatwave occurred. The increased solar radiation accompanied by the weakened wind reduced the vertical mixing and resulted in a thinner mixed-layer, which accelerated the sea surface warming. The impact of reduced mixing is as important as the increase in solar radiation. In mid-August, typhoon-induced entrainment mainly caused sea surface cooling. The wind-driven mechanical mixing between warm surface water and cooler subsurface water lowered the SST. Additionally, evaporative cooling by strong winds, which drives buoyancy-driven vertical mixing, contributed to the decay of the MHW. The effect of mechanical mixing on cooling is comparable to that of buoyancy-driven mixing.